Old dogs—new tricks: immunoregulatory properties of C3 and C5 cleavage fragments. Issue 1 (November 2016) - Verschoor, Admar; Karsten, Christian M.; Broadley, Steven P.; Laumonnier, Yves; Köhl, Jörg
Summary: The activation of the complement system by canonical and non‐canonical mechanisms results in the generation of multiple C3 and C5 cleavage fragments including anaphylatoxins C3a and C5a as well as opsonizing C3b/iC3b. It is now well appreciated that anaphylatoxins not only act as pro‐inflammatory mediators but as immunoregulatory molecules that control the activation status of cells and tissue at several levels. Likewise, C3b/iC3b is more than the opsonizing fragment that facilitates engulfment and destruction of targets by phagocytes. In the circulation, it also facilitates the transport and delivery of bacteria and immune complexes to phagocytes, through a process known as immune adherence, with consequences for adaptive immunity. Here, we will discuss non‐classical immunoregulatory properties of C3 and C5 cleavage fragments. We highlight the influence of anaphylatoxins on Th2 and Th17 cell development during allergic asthma with a particular emphasis on their role in the modulation of CD11b + conventional dendritic cells and monocyte‐derived dendritic cells. Furthermore, we discuss the control of anaphylatoxin‐mediated activation of dendritic cells and allergic effector cells by adaptive immune mechanisms that involve allergen‐specific IgG1 antibodies and plasma or regulatory T cell‐derived IL‐10 production. Finally, we take a fresh look at immune adherence with a particular focus on the development of antibacterial cytotoxic T‐cell responses.